2014
DOI: 10.5070/d3203021769
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the Dutch S3-Guidelines on the treatment of psoriasis 2011

Abstract: This document provides a summary of the Dutch S3-guidelines on the treatment of psoriasis. These guidelines were finalized in December 2011 and contain unique chapters on the treatment of psoriasis of the face and flexures, childhood psoriasis as well as the patient's perspective on treatment. They also cover the topical treatment of psoriasis, photo(chemo)therapy, conventional systemic therapy and biological therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Those treatment differences could, in part, be explained by the specific Dutch guideline on psoriasis, first published in 2003 ( 14 ) and updated at least twice ( 15 , 16 ). In 2003, Dutch dermatologists proposed methotrexate and ciclosporin as the oral treatments for psoriasis, because of a higher efficacy compared with retinoids and fumarates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those treatment differences could, in part, be explained by the specific Dutch guideline on psoriasis, first published in 2003 ( 14 ) and updated at least twice ( 15 , 16 ). In 2003, Dutch dermatologists proposed methotrexate and ciclosporin as the oral treatments for psoriasis, because of a higher efficacy compared with retinoids and fumarates.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be a consequence of updated guidelines, first in 2012 in UK and, secondly, in 2015 at the European level, which proposed methotrexate as the first-choice treatment. In 2011, Dutch guidelines proposed adalimumab or etanercept as first-line biologic agents, because the long-term efficacy and safety profile of ustekinumab were less known compared with those of anti-TNF agents ( 15 ). Despite an update of the Dutch guidelines in 2017, adalimumab and ustekinumab were the first choice of biologic agent, with equal proportions ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Authors concluded that efficacy of Cys-A in childhood psoriasis is "ambiguous" since one case series of 4 young children affected with atypical forms of psoriasis (neonatal, acral, or immunodeficiency-associated) did not show any response [20]. Dutch guidelines duplicated this opinion [24]. Safety issues were sparsely described.…”
Section: Discussionmentioning
confidence: 99%